Concepções de adolescentes autores de ato infracional sobre a escola, 2015 - Lourenção, Elizabeth Soares Pinheiro [UNESP] (2015)
This dissertation had as a general goal to understand the conceptions of transgressor adolescents about school. To this end, we conducted field research in nine adolescents in compliance with socio-educational measures (watched liberty and free services to the community), which were seven boys and two girls. It also participated of this research, nine professionals that work with adolescents who are in the executions process of the socio-educational measures. The research was developed in Presidente Prudente/SP by the Social Assistance Reference Center (Creas), social and educational measures. The selection of subjects surveyed did it by intentional sample, noting the presence of typical elements and features such as involvement with illegal acts and compliance with socio-educational measures in freedom. Despite the relevance of these characteristics, it was considered as the main selection element the will of participation of adolescents in the study. It is a qualitative research in which the theoretical position is deeply aligned with critical theory that prompted us to grasp the essence of the facts, not just what is perceived. Data analysis was built on the triangulation of proposed methods which allowed us the combination of three data collection sources: interview with teenagers; the documentary analysis of the IAP (Individual Care Plan)...